Plan Estratégico para la Empresa E.I.C.Guanacaste S.A. - Ramírez-Masís, Viviam Natalia (Instituto Tecnológico de Costa Rica., 2016)
The present work seeks to present the strategic plan for the company EIC Guanacaste S.A, with the fantasy name of the International Christian School. It is located in the province of Guanacaste, in the canton of Liberia. The institution provides educational services, including pre-school, primary and secondary levels, under US education standards but in turn basic education stipulated by the Ministry of Public Education. EIC Guanacaste does not have strategic objectives that can reach the proposed goals; therefore, it has not well defined what the strategies necessary to reach them are. Hence the importance of seeking to define the direction and strategy that the company must follow in order to achieve its long-term objectives and achieve a competitive advantage over its competitors and to achieve business success.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2016.
Keywords: Organización; Administración; Competencia empresarial; Marketing; Planeamiento estratégico; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies